Tritium Production and Partitioning from the Irradiation of Lithium-Beryllium Fluoride Salt. (19th May 2017) - Carpenter, David; Ames, Michael; Zheng, Guiqiu; Kohse, Gordon; Hu, Lin-wen
Abstract: The MIT Nuclear Reactor Laboratory (NRL) has irradiated lithium-beryllium fluoride (flibe) salt as part of an on-going U.S. Department of Energy-funded Integrated Research Project to develop a Fluoride Salt High-Temperature Reactor (FHR). As part of this project, the NRL has carried out two irradiations of FHR materials in static flibe at 700°C in the MIT Research Reactor. These irradiations marked the start of a program evaluating the tritium production and release from the fluoride salt system at high temperature; in particular, there is interest in the evolution of tritium from the salt into solid materials and cover gasses. This paper describes the experience gained from the irradiation of flibe with respect to the detection of tritium. It covers the development of techniques for monitoring the evolution of tritium from the salt during irradiation and the factors particular to the FHR system that influence this process, including the radiolytic production and release of volatile fluorine and fluoride products as a function of temperature. In addition, it discusses the measurement of tritium partitioning between the different materials in the experiment due to the confluence of diffusion, adsorption, and chemical and radiolytic reactions.